Mutational monitoring of EGFR T790M in cfDNA for clinical outcome prediction in EGFR-mutant lung adenocarcinoma - Su, Kang-Yi (PLoS One, 2018)
Several ultra-sensitive methods for T790M in plasma cell-free DNA (cfDNA) have been developed for lung cancer. The correlation between mutation-allele frequency (MAF) cut-off, drug responsiveness, and outcome prediction is an unmet needs and not fully addressed. An innovative combination of peptide nucleic acid (PNA) and Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) was used to proof of concept for monitoring cfDNA T790M in EGFR-mutant patients. Mutant enrichment by PNA was optimized and the detection limit was evaluated through serial dilutions. The cut-off value was identified by receiver-operating-characteristic (ROC) curve analysis utilizing serial sampled plasmas of patients from EGFR-tyrosine kinase inhibitor (TKI) pretreatment to progressive-disease (PD). Results, comparisons, and objective response rate (ORR) were analyzed in 103 patients’ tumor and cfDNA T790M, with 20 of them receiving an additional COBAS test. The detection limit was 0.1% MAF. The cut-off for PD and imminent PD was 15% and 5% with an ROC area under the curve (AUC) of 0.96 and 0.82 in 2 ml plasma. Detection sensitivity of cfDNA T790M was 67.4% and overall concordance was 78.6%. ORR was similar in T790M-positive cfDNA (69.6%) and tumor samples (70.6%) treated with osimertinib. Among 65 T790M-positive tumors, 15 were negative in cfDNA (23.1%). Seven of 38 T790M-positive cfDNA samples were negative in the tumors (18.4%). PNA-MALDI-TOF MS had a higher detection rate than COBAS. In conclusion, identification of T790M cut-off value in cfDNA improves cancer managements. We provide a strategy for optimizing testing utility, flexibility, quality, and cost in the clinical practice.